Overcoming difficulties with equipoise to enable recruitment to a randomised controlled trial of partial ablation vs radical prostatectomy for unilateral localised prostate cancer. (15th August 2018) - Elliott, Daisy; Hamdy, Freddie C.; Leslie, Tom A.; Rosario, Derek; Dudderidge, Tim; Hindley, Richard; Emberton, Mark; Brewster, Simon; Sooriakumaran, Prasanna; Catto, James W.F.; Emara, Amr; Ahmed, Hashim; et al.
Abstract : Objective: To describe how clinicians conceptualised equipoise in the PART (Partial prostate Ablation vs Radical prosTatectomy in intermediate‐risk unilateral clinically localised prostate cancer) feasibility study and how this affected recruitment. Subjects and Methods: PART included a QuinteT Recruitment Intervention (QRI) to optimise recruitment. Phase I aimed to understand recruitment, and included: scrutinising recruitment data, interviewing the trial management group and recruiters ( n = 13), and audio‐recording recruitment consultations ( n = 64). Data were analysed using qualitative content and thematic analysis methods. In Phase II, strategies to improve recruitment were developed and delivered. Results: Initially many recruiters found it difficult to maintain a position of equipoise and held preconceptions about which treatment was best for particular patients. They did not feel comfortable about approaching all eligible patients, and when the study was discussed, biases were conveyed through the use of terminology, poorly balanced information, and direct treatment recommendations. Individual and group feedback led to presentations to patients becoming clearer and enabled recruiters to reconsider their sense of equipoise. Although the precise impact of the QRI alone cannot be determined, recruitment increased (from a mean [range] of 1.4 [0–4] to 4.5 [0–12] patients/month) and the feasibility study reached its recruitment target. Conclusion: Although clinicians find it challenging to recruit patients to a trial comparing different contemporary treatments for prostate cancer, training and support can enable recruiters to become more comfortable with conveying equipoise and providing clearer information to patients.